Grounding Human Machine Interdependence Through Dependence and Trust Networks: Basic Elements for Extended Sociality - Falcone, Rino; Castelfranchi, Cristiano (Frontiers in Physics, 2022)
In this paper, we investigate the primitives of collaboration, useful also for conflicting and neutral interactions, in a world populated by both artificial and human agents. We analyze in particular the dependence network of a set of agents. And we enrich the connections of this network with the beliefs that agents have regarding the trustworthiness of their interlocutors. Thanks to a structural theory of what kind of beliefs are involved, it is possible not only to answer important questions about the power of agents in a network, but also to understand the dynamical aspects of relational capital. In practice, we are able to define the basic elements of an extended sociality (including human and artificial agents). In future research, we will address autonomy.